Structural and functional differences of cytosolic 90-kDa heat-shock proteins (Hsp90s) in Arabidopsis thaliana - Cha, Joon-Yung (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 The Authors. Published by Elsevier Masson SAS.. All rights reserved.